New fossils from Tadkeshwar Mine (Gujarat, India) increase primate diversity from the early Eocene Cambay Shale. Issue 122 (September 2018) - Rose, Kenneth D.; Dunn, Rachel H.; Kumar, Kishor; Perry, Jonathan M.G.; Prufrock, Kristen A.; Rana, Rajendra S.; Smith, Thierry
Abstract: Several new fossil specimens from the Cambay Shale Formation at Tadkeshwar Lignite Mine in Gujarat document the presence of two previously unknown early Eocene primate species from India. A new species of Asiadapis is named based on a jaw fragment preserving premolars similar in morphology to those of A. cambayensis but substantially larger. Also described is an exceptionally preserved edentulous dentary (designated cf. Asiadapis, unnamed sp. nov.) that is slightly larger and much more robust than previously known Cambay Shale primates. Its anatomy most closely resembles that of Eocene adapoids, and the dental formula is the same as in A. cambayensis . A femur and calcaneus are tentatively allocated to the same taxon. Although the dentition is unknown, exquisite preservation of the dentary of cf. Asiadapis sp. nov. enables an assessment of masticatory musculature, function, and gape adaptations, as well as comparison with an equally well-preserved dentary of the asiadapid Marcgodinotius indicus, also from Tadkeshwar. The new M . indicus specimen shows significant gape adaptations but was probably capable of only weak bite force, whereas cf. Asiadapis sp. nov. probably used relatively smaller gapes but could generate relatively greater bite forces.